Analisis Instrument Evaluasi Maharatul Istima Didalam Buku Bahasa Arab Kls VII Madrasah Tsanawiyah - Bukhari; Hikmah; Masrun (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2025)
This study aims to understand and analyze the evaluation instrument of istima' skills in Arabic language learning for grade VII of Madrasah Tsanawiyah. This study is a library research with a qualitative approach, where data is collected from various literature sources such as textbooks, scientific articles, and academic journals. Data analysis uses the content analysis method, which involves data processing, in-depth reading, description, and interpretation of data to produce a comprehensive understanding. The results of the study indicate that although there have been various efforts in developing the maharatul istima' evaluation instrument, its implementation in the field still faces various challenges, such as limitations in compiling valid questions, selecting the right audio material, and technical obstacles when using technology. However, the Arabic language book for grade VII of Madrasah Tsanawiyah has implemented the istima' evaluation form in various exercise formats such as answering oral questions based on text, multiple choice questions, completing sentences with isim isyarah, and giving marks according to or not according to the conversation heard. This study is expected to be the basis for developing more effective and contextual evaluation instruments in improving students' listening competence in Arabic.